Analisis kecerdasan interpersonal dalam proses pembelajaran peserta didik kelas III Ibrahim Di SDIT Atikah Musaddad - Muhammad Nurjamaludin; Maulida Aulia Rahman; Ramila Nuraeni; Indah Permata Sari (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
This study aims to describe variations in interpersonal intelligence during the learning process of Grade III students. It is motivated by the importance of developing social skills such as cooperation, communication, and empathy. The research uses a qualitative phenomenological approach, with data collected through interviews and documentation. The subjects include five third-grade students from Ibrahim, selected using an interpersonal intelligence questionnaire, along with four teachers and the principal. The findings are analyzed through indicators of interpersonal intelligence: social sensitivity, social insight, and social communication. The results show variations among students; some demonstrate strengths in all areas, while others excel in certain aspects but need support in others. School policies and programs play a crucial role in fostering these skills. Strategies such as positive social habituation, collaborative learning, character education integration, and active involvement of the school community and parents are essential to support the development of students' interpersonal intelligence.